Validation of the French Version of Conners' Parent Rating Scale–Revised, Short Form in ADHD-Diagnosed Children and Comparison With Control Children. Issue 1 (January 2021) - Fumeaux, Pierre; Mercier, Catherine; Roche, Sylvain; Iwaz, Jean; Stéphan, Philippe; Revol, Olivier
Objective: The objective of this study was to examine measurement invariance and discriminant validity of the French Lausanne version (FLV) of the Conners' Parent Rating Scale–Revised, Short Form (CPRS-R:S) and assess its convergent validity against the ADHD Symptoms Rating Scale (ADHD-SRS) and the Child Behavior Checklist (CBCL).Method: A confirmatory factor analysis and Tobit models were used in 108 ADHD children (aged 6-17) vs. 794 controls (aged 9-15) and score correlations were examined between FLV and ADHD-SRS then CBCL.Results: The factorial structure and reliability of the FLV is confirmed in ADHD children. The FLV showed configural invariance, metric invariance, and scalar invariance. FLV scores were significantly higher in ADHD than in control children in all three dimensions ( p < .001). There were strong correlations between FLV Hyperactivity and Cognitive problems/Inattention scores and ADHD-SRS scores of Impulsivity/Hyperactivity ( r = .90) and Inattention ( r = .68) and also strong correlations between FLV Opposition score and the CBCL scores of Aggressive behavior ( r = .84) and Rule-breaking behavior ( r = .66).Conclusion: The study brings support for validation of the FLV regarding invariance in ADHD children, discriminant validity, and convergent validity.